The Role Of School Leaders In Effective Educational Management A Case Study Of Jordan - Hussien Shafi’ Abedalaziz Alkayed (International Journal of Advanced Science and Technology, 2020)
The diligence of every school is manifested in the outcome of her students. Excellent outcome can only be achieved when effective and judicious means are put in place to accomplish these ends; those effective parameters among others, start with effective leadership and also include management distinctions such as the commitment of staff members to work extra mile, their consistency in delivering excellent services and the support of the community to ensure serene environment for learning. For a school to have a successful outcome, it depends on the structure, disciplines and beneficence factored into the system of the school that become guidelines for the staff members and students to follow so that the vision of the school will be accomplished. The staff members of a school will be willing and ready to deliver excellent services irrespective of inconveniencies as long as the factors aforementioned are judicially combined. By conducting extra lessons without extra payment, outstanding schools produce outstanding students. The syllabus is completely taught with additional effort, workable plans are in place to be followed with adequate materials to use effectively. Continuous assessments are painstakingly structured with proper monitoring by the leaders in charge. They solve matters arising and implement strategies to curb such matters. The challenge that can be faced in an outstanding school is much work to do within limited time. The members of staff, students and community are engaged with precise comprehension of their duties. Instructional leadership, team leadership and distributed leadership styles are major leadership styles mentioned to achieve effective educational management in this study.